Efficacy and Safety of Flexible Laryngeal Mask Ventilation in Otologic Surgery: A Retrospective Analysis - Liu F; Xi C; Cui X; Wang G (Dove Medical Press, 2022)
Feihong Liu, Chunhua Xi, Xu Cui, Guyan Wang Department of Anesthesiology, Beijing Tongren Hospital, Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Guyan Wang, Department of Anesthesiology, Beijing Tongren Hospital, Capital Medical University, Beijing, People's Republic of China, Tel +86-13910985139, Email Guyanwang2006@163.comBackground: Flexible laryngeal mask airways (FLMAs) ventilation have been widely used as airway devices during general anesthesia, especially in otologic surgery. However, the current literature reports that the clinical success and failure rates for FLMA usage are quite different, and there remains a paucity of data regarding factors associated with FLMA failure and complications related to FLMA usage.Purpose: To evaluate the success and failure rates of FLMA usage in otologic surgery, the factors associated with FLMA failure and complications related to FLMA usage.Patients and Methods: All patients who underwent otologic surgery, including middle ear and mastoid procedures, under general anesthesia at a large tertiary general hospital from 2015 to 2019 were reviewed. The primary outcome was the FLMA failure rate, defined as any airway event requiring device removal and tracheal intubation, including primary and secondary failure. The secondary outcomes were specific clinical factors, including patient sex, age, weight, American Society of Anesthesiologists (ASA) classification, body mass index (BMI) and duration of surgery, which were analyzed as related risk factors.Results: Among 5557 patients with planned FLMA use, the final success rate was 98.5%. Sixty-seven percent of the failures occurred during initial introduction of the FLMA, 8% occurred after head and neck rotation, and 25% occurred during the procedures. Two independent clinical factors associated with FLMA failure were male sex and age. Respiratory complications were observed in 0.61% of patients, and the rate of severe nerve and tissue damage associated with FLMA use was 0.05.Conclusion: This study demonstrates a high success rate of 98.5% for FLMA use in adults undergoing otologic surgery with rare adverse airway events and injuries complications. Two independent risk factors require attention and thorough and accurate management is necessary for every clinician.Keywords: otologic surgery, flexible laryngeal mask airway, safety, efficacy, airway complications